‘They Carried the Land Itself’: Eco-Being, Eco-Trauma, and Eco-Recovery in Tim O’Brien’s The Things They Carried: English - Cochran, James (Journal of Ecohumanism, 2022)
This essay calls for a wider use of Tina Amorok’s (2007) concepts of eco-Being, eco-trauma of Being, and eco-recovery of Being in ecocritical literary studies. I propose the adoption of Amorok’s concepts as a literary hermeneutic because it provides a theoretical model that positions ecological damage as central to wartime trauma. To demonstrate the effectiveness of Amorok’s framework, the following essay reads Tim O’Brien’s 1990 novel The Things They Carried alongside Amorok’s eco-Being, eco-trauma, and eco-recovery. Reading O’Brien’s text through Amorok’s model is particularly intriguing and noteworthy because almost no critics investigate the ecocritical dimensions of O’Brien’s novel. Yet, despite the absence of green scholarship surrounding O’Brien’s novel, Amorok’s framework, as I will show, draws attention to the environmental costs of war as depicted in O’Brien’s novel. Applying Amorok’s model as an ecocritical lens to The Things They Carried demonstrates how we can use Amorok’s tripartite structure to further unpack the ecological dimensions of fiction that seemingly have little to do with the environment.